15 years of NATO and EU membership - Veebel, Viljar (Sodobni vojaški izzivi, 2019)
Although the Baltic countries are granted security guarantees within the NATO framework, as well as through active cooperation at the EU level in the field of security and defence policy, enhancing security in the Baltic Sea region, Estonia, Latvia, and Lithuania are still very vulnerable to Russian actions and interventions. They constitute Russia's direct point of contact with both NATO and the EU and are, therefore, among the primary subjects to the interests of Russia to test mutual capabilities and to send strategic messages to its "opponents". This article offers an in-depth comparison of the security threats, national security strategies, country-specific defence models, and expectations of strategic partnership of the Baltic countries.
Keywords: Baltic states; Baltske države; defence; nacionalna varnost; Nato; obramba; Rusija; Russia; security; varnostna politika; vojska